(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study focused on the development of leadership skills through internship as perceived by business education students in universities in Anambra State. One research question guided the study while one null hypothesis was tested at 0.05 level of significance. The study adopted descriptive survey research design. The population of the study consisted of 619 business education students in the three universities offering the programme. The entire population was used for the study. A structured questionnaire was the instrument used for data collection. The reliability of the instrument was established using Cronbach’s alpha and it yielded an overall coefficient of 0.81. Mean and standard deviation were used to analyse data to answer the research question and determine the cohesiveness or otherwise of respondents’ mean rating. ttest was used to test the null hypothesis. The findings of the study revealed that the students perceive internship as a model for the development of leadership skills. However, the result shows that male and female business education students differ significantly in their mean ratings regarding how they perceive the development of leadership skills in internship. Based on the finding, it was concluded that business education students perceive internship as a model that will increase leadership skill development. Consequently, it was recommended among others that there is need for a structured leadership skill acquisition programme for business education students